Study of cutting forces and surface roughness in milling of Carbon Fibre Composite (CFC) with conventional and pressurized CO2 cutting fluids - Dahnel, Aishah Najiah; Barnes, Stuart; Kibbler, Christopher; Ascroft, Helen (American Society of Mechanical Engineers (ASME), 2015)
Carbon Fibre Composites (CFC) are commonly used in aerospace, automotive and civil industries to manufacture high performance products which require high strength with low weight. They are usually produced to near net shape, however machining such as milling is frequently performed to achieve dimensional accuracy. This paper presents the effect of using conventional (water-based) and carbon dioxide (CO2) cutting fluids during milling of CFC on cutting forces, temperature and surface roughness in comparison to dry milling. Milling experiments were conducted using uncoated tungsten carbide milling routers at a constant feed rate and depth of cut of 0.025 mm/rev and 5 mm, respectively. Cutting speeds used were 100, 150 and 200 m/min. Cutting forces were measured using a dynamometer, temperatures during milling were measured at the workpiece by thermocouples and surface roughness (Ra) of the milled surfaces were measured using a surface profilometer. Milling with conventional and CO2 cutting fluids resulted in higher cutting forces than dry milling at all cutting speeds used. This was attributed to cooling of the CFC, which retained the strength of polymer matrix during machining. Cutting temperatures were the highest and reached beyond 100ºC during dry milling. The use of conventional cutting fluid during milling provided significant cooling to the workpiece, in which cutting temperatures were maintained below 30ºC at all cutting speeds used. Cooling the workpiece during milling with CO2 cutting fluid resulted in cutting temperatures within the range of 65 – 86ºC. Even though the application of cutting fluids during milling generated higher cutting forces than dry milling, it produced favourable results in terms of surface finish. The use of cutting fluid during machining CFC is shown to be highly effective in sustaining the strength of CFC materials as a result of low cutting temperature.